Crystallographic texture of materials - Suwas, Satyam (Engineering Materials and Processes,, 2014)
Providing a comprehensive and invaluable overview of the basics of crystallographic textures and their industrial applications, this book covers a broad range of both structural and functional materials. It introduces the existing methods of representation in an accessible manner and presents a thorough overview of existing knowledge on texture of metallic materials. Texture analysis has widespread use in many industries, and provides crucial input towards the development of new materials and products. There has been rapid growth in the science and art of  texture analysis in the last few decades. Other topics addressed within this book include recent research on texture in thin films and non-metals, and the dependence of material properties on texture, and texture control in some engineering materials. This book constitutes an invaluable reference text for researchers and professionals working on texture analysis in metallurgy, materials science and engineering, physics and geology. By using content selectively, it is also highly accessible to undergraduate students.